An Examination of Parental Engagement in Young Learner EFL Literacy Development - Widyo Heryadi; Pratiwi Retnaningdyah (Institut Agama Islam Negeri Madura, 2024)
Abstract: This study examines a home reading and writing practices of a family in Balongpanggang, Gresik. Researcher uses a qualitative approach. The ORIM frame work permits us to look at this engagement. From this think about of this families, it is evident that family tend to recognize his/her children's new-to-her EFL scholarly improvement. In spite of the fact that there are diverse engagement strategies such as considering diverse choices, appearing appreciation, interfacing with children, and taking portion in exhibitions. The survey results and parent interviews revealed how parents perceive their involvement in the EFL development of young learners and how they are involved in the development of young learners' EFL literacy. It is utilized to depict whether Analysts found that whereas families see their child's developing proficiency hones more customarily, they still provide opportunities,, recognize their development, interact with them, and improve the child's EFL literacy. Found that it served as a role model for the learning of Recognition of these family engagement strategies highlighted the complexity of the literacy process and emphasized the importance of the whole family in helping the young learner develop her EFL literacy skills.